Avaliação de cartilha virtual sobre autoexame ocular para portadores de HIV/AIDS - Lima, Maria Alzete de (2011)
A significant proportion of individuals at different stages of evolution of HIV infection presents irreversible eye changes due to lack of early diagnosis and treatment, sometimes these changes cause loss of visual acuity. Therefore, a printed guide on eye self-examination was developed, and aiming to increase the access to this material it was developed for a digital environment, which is justified by the need to increase the knowledge on eye self-examination and the adherence to this practice. Thus it was aimed to assess the distance education technology for the eye health promotion; match the printed material to the virtual; assess the Virtual Guide on Eye Self-examination of expert judges on pedagogical and technical aspects. It is a study to develop digital educational material proposed by Falkembach, with the following stages: preparation of digital educational material, modeling phase, implementation, distribution and assessment. It was developed at the Laboratory of Health Communication, Federal University of Ceará from 2009 to 2010. In the first phase the development of digital material was done, then it was submitted to the initial trial of nursing students in order to identify difficulties in the use of material created, and the language adjustment of the digital educational material was made. In the final stage it was submitted to the assessment by expert judges in the area of education and IT. As a result it was possible to identify flaws in the initial structuring of pages, and commands had to be replaced, unified and arranged in places of easy viewing. Therefore, the digital material was reformulated in order to be appropriate to the virtual environment, including restructuring the language. The choice for the tutorial video was proved to be an effective tool for individual training, and promoted greater autonomy for the fact that supports the achievement of eye examinations by the user. In the assessment of interviews the material was proved to be easy to navigate and able to arouse curiosity and interest in accessing the content considered by the evaluators easy to understand. It is important to use new care technologies focused on educational actions, however, it requires a complete assessment of its limitations, benefits and an adjustment to the needs of users, once it is a continuous process of improvement and adjustment, and so propose an innovative way to generate conscious and intentional attitudes, as well as appreciation and recognition of the exercise of citizenship. We hope that the virtual guide on eye self-examination facilitates the identification of visual changes and also provides stimulus to search for eye care, indispensable aspect in AIDS